Organization legal providing of law enforcement on the territories of the western areas of Ukraine in aperiod from 1944 till 1948 - Резницька, Вікторія Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In the article describes the issues about the organizational support of the public order group in the westernregions of Ukraine.